Learning Creative Problem-Solving Model With Guided Inquiry Strategy to Improve Students' Concept Mastery - Kurnia, Tri Santi; Leiwakabessy, Fredy; Awan, Ali; Kotala, Sarmawaty (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2024)
Categories of learning outcomes include acceptance, response, assessment, organization, and pattern formation. Thus, the essence of learning is a change in thinking that affects behaviour. The results of interviews with teachers at SMA Kartika XIII-I Ambon show that current students have not shown an environmentally conscious attitude. Therefore, research was conducted to improve the mastery of the concept of class X students on environmental pollution material using creative problem-solving learning models with guided inquiry strategies. This study used a classroom action research method that took place in two cycles for one month. The subjects in this study were 26 students. The research data were processed descriptively on the results of cognitive, affective, and psychomotor assessments. The results showed that in cycle I there were still 65.4% of students who had not achieved mastery of concepts on environmental pollution material. Therefore, the research was continued in cycle two with the action of using the creative problem-solving learning model based on guided inquiry strategy and coupled with audio-visuals media, as well as a stimulus in the form of giving rewards to active students. It was proven that in cycle II there was an increase in students' mastery of concepts in environmental pollution material in students by 100% so that the series of class action research was no longer continued. In conclusion, the use of learning models